Family Business Succession Planning at PT. X - Nourmalasari, Raisha Dian (International Journal of Review Management Business and Entrepreneurship (RMBE), 2022)
The purpose of this research is to know succession planning from the second generation to the third generation in PT. X. This research is descriptive quantitative, which is research that produces descriptive data in the form of written or spoken words from informants and understands the behavior of individuals and groups that can be observed. The data obtained were collected and analyzed by interview and observation to six informants from PT. X is three of the second generation, and three of the third generation with triangulation analysis techniques. The result of this research the role of succession in the third generation of PT. X which includes pre-succession, succession planning, and succession management is already at the pre-succession stage that can support the sustainability of PT. X so that the company's condition can run well.